1988
DOI: 10.1161/01.str.19.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in thyrotoxicosis with atrial fibrillation.

Abstract: Chronic atrial fibrillation is associated with an increased risk of stroke. In elderly patients with thyrotoxicosis, atrial fibrillation is frequently encountered, and the true risk of cerebrovascular events in these patients is controversial. We retrospectively studied 610 patients with initially untreated thyrotoxicosis, 91 (14.9%) of whom had atrial fibrillation, with the highest frequency in the elderly patients. The risk of cerebro vascular events, with special attention to the first year after the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
18

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 21 publications
5
93
1
18
Order By: Relevance
“…Twelve of 30 patients in AF had an embolic event (40%) compared with none in sinus rhythm (112 patients); the mean age of the patients in AF was significantly higher than those in sinus rhythm (56 vs 39 years). A further retrospective study investigating 610 patients with thyrotoxicosis, indicated that age -rather than the presence of AF -was the main risk factor for embolisation, a finding which may be explained by the relatively small number of patients in AF (Petersen & Hansen 1988). Twelve (13%) of those in AF had an embolic event compared with 15 of the 519 patients (2·9%) in sinus rhythm.…”
Section: Thyroid Hormone and The Heartmentioning
confidence: 96%
“…Twelve of 30 patients in AF had an embolic event (40%) compared with none in sinus rhythm (112 patients); the mean age of the patients in AF was significantly higher than those in sinus rhythm (56 vs 39 years). A further retrospective study investigating 610 patients with thyrotoxicosis, indicated that age -rather than the presence of AF -was the main risk factor for embolisation, a finding which may be explained by the relatively small number of patients in AF (Petersen & Hansen 1988). Twelve (13%) of those in AF had an embolic event compared with 15 of the 519 patients (2·9%) in sinus rhythm.…”
Section: Thyroid Hormone and The Heartmentioning
confidence: 96%
“…It may be that a combination of genomic and nongenomic actions on atrial ion channels plus the enlargement of the atrium as a result of the expanded blood volume are the underlying causes. 6,50 It has been suggested that hyperthyroidism resembles a hyperadrenergic state; however, no evidence suggests that thyroid hormone excess enhances the sensitivity of the heart to adrenergic stimulation. 51 In hyperthyroidism, serum levels of catecholamines remain low or normal.…”
Section: Direct Effects Of Thyroid Hormone On the Heartmentioning
confidence: 99%
“…87 Anticoagulation of patients with hyperthyroidism and atrial fibrillation is controversial. 1,50 The risk of systemic or cerebral embolization must be weighed against the potential for bleeding and other complications of this therapy. The risk for systemic embolization in the setting of thyrotoxicosis is not precisely known.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…Caso haja necessidade de manutenção do digital, deve-se lembrar da necessidade de doses maiores em função do hipertiroidismo concomitante. Há controvérsias em relação à necessidade de anticoagulação de pacientes com FA secundárias a hipertiroidismo (14), mas dados sugerem que esses pacientes não apresentam risco de tromboembolismo maior que os com FA por outras causas, notadamente nos pacientes com menos de 55 anos de idade (15). Como se tratava de um paciente jovem, no qual foi realizado ecocardiograma transesofágico que não evidenciou trombos, foi optado por não iniciar anticoagulação com cumarínicos, sendo mantido apenas AAS em dose baixa.…”
Section: Discussionunclassified